Location of stimuli-responsive peptide sequences within silk-elastinlike protein-based polymers affects nanostructure assembly and drug–polymer interactions. (13th September 2020) - Isaacson, Kyle J.; Jensen, M. Martin; Steinhauff, Douglas B.; Kirklow, James E.; Mohammadpour, Raziye; Grunberger, Jason W.; Cappello, Joseph; Ghandehari, Hamidreza
Abstract: Silk-elastinlike protein polymers (SELPs) self-assemble into nanostructures when designed with appropriate silk-to-elastin ratios. Here, we investigate the effect of insertion of a matrix metalloproteinase-responsive peptide sequence, GPQGIFGQ, into various locations within the SELP backbone on supramolecular self-assembly. Insertion of the hydrophilic, enzyme-degradable sequence into the elastin repeats allows the formation of dilution-stable nanostructures, while insertion into the hydrophobic silk motifs inhibited self-assembly. The SELP assemblies retained their lower critical solution temperature (LCST) thermal response, allowing up to eightfold volumetric changes due to temperature-induced size change. A model hydrophobic drug was incorporated into SELP nanoassemblies utilising a combination of precipitation, incubation and tangential flow filtration. While the nanoconstructs degraded in response to MMP activity, drug release kinetics was independent of MMP concentration. Drug release modelling suggests that release is driven by rates of water penetration into the SELP nanostructures and drug dissolution. In vitro testing revealed that SELP nanoassemblies reduced the immunotoxic and haemolytic side effects of doxorubicin in human blood while maintaining its cytotoxic activity.